2019
DOI: 10.1002/14651858.cd012643.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interim PET-results for prognosis in adults with Hodgkin lymphoma: a systematic review and meta-analysis of prognostic factor studies

Abstract: Interim PET-results for prognosis in adults with Hodgkin lymphoma: a systematic review and meta-analysis of prognostic factor studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 234 publications
0
29
1
1
Order By: Relevance
“…[ 18 F]FDG PET/CT is used to accurately stage and assess treatment response in almost all cancers, including those in pediatric patients [ 9 12 ]. However, for pediatric bone and soft tissue sarcoma, the role of [ 18 F]FDG PET/CT is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FDG PET/CT is used to accurately stage and assess treatment response in almost all cancers, including those in pediatric patients [ 9 12 ]. However, for pediatric bone and soft tissue sarcoma, the role of [ 18 F]FDG PET/CT is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PET response-adapted therapies have been assessed to improve efficacy and avoid toxicity. In addition to four studies reporting patients' response to PET responseadapted therapy [60,61,68,73,78], two recent SLRs have investigated PET and HL; one on interim PET results and prognosis concluded that negative interim PET results have a large advantage in terms of OS (moderate certainty evidence) [134]. A review of PET-adapted therapy for HL recommended a PET treatment approach as standard of care for advanced HL [135].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, early monitoring of chemosensitivity by PET‐2, can also enable dose de‐escalation by switching from eBEACOPP to ABVD, to reduce toxicity without loss of disease control 19 . However, among patients with a negative PET‐2 (as indicated by a DS of 1, 2, or 3), approximately 15% will eventually relapse or progress after the end of treatment, and only 60% to 67% are expected to be rescued by the more toxic regimen eBEACOPP at three to 5 years 20‐22 . Thus, PET‐2 has limited value for identify patients who will achieve long‐lasting complete remission (CR).…”
Section: Introductionmentioning
confidence: 99%